2015
DOI: 10.1016/j.chemer.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Chondrule size and related physical properties: A compilation and evaluation of current data across all meteorite groups

Abstract: Please cite this article in press as: Friedrich, J.M., et al., Chondrule size and related physical properties: A compilation and evaluation of current data across all meteorite groups. Chemie Erde -Geochemistry (2014), http://dx.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
116
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(141 citation statements)
references
References 94 publications
(273 reference statements)
23
116
2
Order By: Relevance
“…The average chondrule size (~500 μm) is closest to that of mean LL chondrites (550 μm; table 7 of Friedrich et al. ). The mean olivine composition (Fa 28.1 ± 1.8; PMD = 5.1; n = 16) and mean kamacite Co content (1.5 ± 0.9 wt%; n = 7) are well within the equilibrated LL chondrite ranges (Fa 26.6–32.4; 1.42–37.0 wt% Co; Rubin ).…”
Section: Resultsmentioning
confidence: 61%
“…The average chondrule size (~500 μm) is closest to that of mean LL chondrites (550 μm; table 7 of Friedrich et al. ). The mean olivine composition (Fa 28.1 ± 1.8; PMD = 5.1; n = 16) and mean kamacite Co content (1.5 ± 0.9 wt%; n = 7) are well within the equilibrated LL chondrite ranges (Fa 26.6–32.4; 1.42–37.0 wt% Co; Rubin ).…”
Section: Resultsmentioning
confidence: 61%
“…), which is comparable to the value from R chondrites (400 μm), but differs from the values of CH (20 μm), CO (150 μm), CB (200 μm), CR (700 μm), and CV/CK (900 μm) chondrites, as well as chondrule average diameters from ordinary chondrites (450–550 μm) (Friedrich et al. ). Of Y‐82094 chondrules, 99.1% are FeO‐poor (defined as those with Mg# silicate >90; Mg# = mole% MgO/[MgO + FeO]); FeO‐rich chondrules (Mg# silicate <90) are sparse (0.9%).…”
Section: Introductionmentioning
confidence: 49%
“…It is worth noting in this regard that in their numerous publications on iron droplets, Friedrich et al, (2015) support the idea that these grains were formed via condensation, that is, are nebular in origin. There is no logical reason why the reduction of oxides (equilibrium reaction (1)) could not also be associated with the condensation processes occurring in a cooling gas of cosmic composition.…”
Section: Argument 8: Chromium Copper and Dual-concentration Valuesmentioning
confidence: 89%
“…In the case of equilibrium reaction (1), age determination begins with the mobilization process itself; for equilibrium reaction (2), age determination begins prior to mobilization, as the iron was already separate from the silicate phase before mobilization began. Information on the origins of the metal phase in chondrites has been provided by Ebihara (1996, 1997), Davis and Richter (2014) and Friedrich et al (2015). Further insight is likely to be gained if it can be shown that the series ataxites, Of, Off, Om, Ogg, H, Og (see Argument 7) is connected to trends in the absolute ages of these meteorites.…”
Section: Argument 13: Cosmochronologymentioning
confidence: 99%